MEMBANGUN KESADARAN HUKUM ANAK DI PANTI ASUHAN ASY-SYIFA’ TERHADAP BULLYING DI LINGKUNGAN SEKOLAH DAN MASYARAKAT: Building Legal Awareness Of Children In Asy-Syifa Orphanage' Against Bullying In The School And Community Environment - Harun, Rina Rohayu; Septyanun, Nurjannah; Erwin, Yulias; Supryadi, Ady; Yamin, Bahri; Yuliani, Tin; Fahrurrozi, Fahrurrozi; Aminwara, Rena; Mantika, Aesthetica Fiorini; Ariani, Zaenafi (Al-Amal: Jurnal Pengabdian Masyarakat, 2024)
Cases of violations of child protection. Of the reports received, 837 cases occurred within the education unit, including: Children who were victims of bullying or harassment: 87 cases, Children victims of educational policies: 27 cases, Children victims of physical and/or psychological violence: 236 cases and Children victims of sexual violence: 487 cases. From data collected by the Indonesian Child Protection Commission (KPAI) and the Federation of Indonesian Teachers' Unions (FSGI), bullying cases are still a terror for children in the school environment. Meanwhile, the types of bullying that victims often experience are physical bullying (55.5%), verbal bullying (29.3%), and psychological bullying (15.2%). Meanwhile, regarding educational level, elementary school students were the most victims of bullying (26%), followed by middle school students (25%), and high school students (18.75%). The aim of this service is to provide education to participants in community service activities so that bullying does not occur at school. The method used is a socialization method carried out face to face. The results are 50%. Orphaned children do not understand the limits of bullying itself, and their rights as children and citizens, despite the social and economic disparities they have. Some of the orphanage children are still insecure about their condition of not having parents, or having incomplete parents. So they tend to tolerate what happens to them, because they are not aware of these rights and also their own condition.